Evaluation of Surgical Outcome of Pelviureteric Junction Obstructive Patients by 99mTc-DTPA Renography - Sultana, Tania; Hossain, Md Sanowar; Sultana, Sadia; Akhter, Afroza; Sharmin, Shaila; Rahman, Farhana; Hossain, Sadia; Hossain, Mohana; Afrin, Rawnak; Biswas, Shankar Kumar; et al. (Bangladesh Journal of Nuclear Medicine, 2024)
Objectives: Pelviureteric junction (PUJ) obstruction is the most common congenital abnormality of urinary tract and accounts for about 80% cases. 99mTc-DTPA renography with diuretic challenge helps to distinguish obstructive hydronephrosis from non-obstructive calyceal dilatation and also allows the surgeons to select cases for surgical intervention. This study aims to compare and evaluate the surgical outcomes of PUJ obstructive patients by 99mTc-DTPA renography. Patients and Methods: This prospective, longitudinal study was carried out at the Institute of Nuclear Medicine & Allied Sciences (INMAS), Dhaka, during July 2016 to June 2017 and 99mTc-DTPA renography was done in diagnosed cases of PUJ obstruction (diagnosed by ultrasonography and intravenous urography) before and 3 months after Anderson Hynes (A-H) pyeloplasty. Static renal imaging was also done after 1 and 2 hours after the dynamic acquisition to compare the pre and postoperative anatomical findings. The study included a total of 70 patients with PUJ obstruction before and after A-H pyeloplasty. Patients with GFR < 10 ml/min, serum creatinine level > 3 mg/dl and pregnancy were excluded. Result: In this study, 70 (100%) of the preoperative patients had obstructive uropathy. Following surgery, 31 patients (44.3%) had obstructive uropathy, 22 patients (31.4%) had partial obstruction, and 17 patients (24.3%) had functional obstruction. Before surgery, the individuals’ mean differential renal function (%) was 38.7 ± 8.2, and after surgery, it was 41 ± 9.8. In preoperative subjects, the mean glomerular filtration rate (ml/min) was 42.1 ± 9.1, while in postoperative ones, it was 46.2 ± 10.8. In preoperative subjects, the mean total glomerular filtration rate (ml/min) was 92.1 + 8.9, while in postoperative ones, it was 95.5 ± 10.4. The pre- and postoperative DTPA renography results differed in a statistically significant way (p < 0.05). Before surgery, the patients had a mean serum creatinine (mg/dl) of 1.3 ± 0.4, and after surgery, it was 1.2 ± 0.4. The pre- and postoperative differences were not statistically significant (p > 0.05). Static images of the DTPA renogram acquired one and two hours in post pyeloplasty patients revealed the characteristics of obstruction. Three months after the pyeloplasty, 23 (32.9%) of the participants had stable renal function, 36 (51.4%) had improved renal function, and the remaining 11 (15.7%) had worsened renal function in 99mTc-DTPA renogram. Conclusion: Most of the study subjects showed improved renal parenchymal function and glomerular filtration rate (GFR) in post pyeloplasty 99mTc-DTPA renograms at 3 months. Routine 99mTc-DTPA renogram of all the patients with PUJ obstruction before and after the pyeloplasty might be beneficial for further management as it is a simple, non-invasive, cost-effective technique with low radiation exposure. Bangladesh J. Nuclear Med. 27(1): 16-20 , 2024